Africa’s Underdevelopment: Does Africa Need Western Prescriptions? - Mafa, Mafa Kwanisai (Modern Ghana, 2020)
The African continent is the biggest continent on earth endowed with immense natural and human resources .Africa has the youngest population on earth. It is also endowed with great cultural, ecological and economic diversity but paradoxically it remains the poorest continent on earth. The United Nations classifies Africa as the most least developed.